Tax professionals' views on self assessment system - Kasipillai, Jeyapalan; Mohd Hanefah, Mustafa (Universiti Utara Malaysia, 2000)
Malaysia has adopted an Official Assessment System (OAS) whereby taxpayers were assessed by the tax authorities based on the tax returns filled by them. The Malaysian Government has introduced a Self Assessment System (SAS) in stages commencing with companies from 2001. This new strategy require taxpayers to take more responsibility for getting their tax returns correct, since the information which they furnish in their returns will be accepted at face value by the Inland Revenue Board (IRB). The IRB, however, will audit some cases at random and if it has inaccurate information, the taxpayers concerned will be liable for prosecution.This survey focuses on the role of tax professionals under SAS. The findings of the survey reports on tax professionals' views and level of preparation towards the implementation of SAS in Malaysia. The findings also report on problems faced by tax professionals under the existing official assessment tax system and seek to ascertain tax professionals' perception towards the introduction of the new assessment system. Finally, the data provides some input on the preparatory measures to be undertaken by the IRB to facilitate tax practitioners' role in enhancing tax compliance under the new assessment system.